Análisis del mantenimiento preventivo en los camiones mineros 980 E-5 y su relación con la disponibilidad mecánica - Baldeon Pacheco, Adrian Pedro (2025)
The processes of the mining industry operate on a large scale, as well as its equipment, personnel, and facilities. It is necessary to plan the work and activities to measure and control its operations. In this sense, mining trucks are a fundamental piece of the board. One of the key indicators for assessing the maintenance process management is availability. To this end, a study and analysis of the performance of 980 E-5 mining trucks has been carried out, obtaining results of key indicators to measure and compare the productivity of the fleet. The quantitative method was applied, with notable results including a 20% increase in mean time between failures (MTBF), indicating improved mean times between truck failures. Mean Time to Repair (MTTR) experienced a slight 5.7% increase in repair time compared to the previous year. Availability saw a 3.3% increase from the contractual value of 91.18%. This was evidenced in the compliance and precision of preventive maintenance with an average frequency of 508 hours in total between each preventive maintenance.